Enhancing Diatomaceous Earth Characteristics for Adsorption of Heavy Metals from Acid Mine Drainage: The Impact of Dual Activation Process - Chalid Muksin; Farid Mulana; Nasrullah Nasrullah; Azwar Azwar; Aulia Chintia Ambarita; Muhammad Prayogie Aulia (Jurnal Rekayasa Kimia & Lingkungan)
This study investigates the effects of dual activation methods, including physical and chemical processes, on the characteristics of diatomaceous earth (DE) for the purpose of controlling heavy metal concentration in acid mine drainage. The DE is subjected to physical activation through calcination at 750 oC for 60 minutes, followed by chemical activation using 1N HCl at 80 oC for 24 hours under magnetic stirring. The resulting adsorbent is then characterized using XRD, SEM-EDX, and BET instruments. The analysis reveals that the dual activation methods increase the silica content and eliminate impurities in the DE, leading to a more amorphous structure with decreased crystallinity. The physical activation increases the surface area, while the dual activation process reduces the surface area and increases pore size. These findings provide valuable insights into the adsorption capacity of DE for reducing heavy metals in acid mine drainage.